2021
DOI: 10.3390/genes12030332
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genomics to Understand Salt Tolerance in Lentil

Abstract: Soil salinity is a major abiotic stress, limiting lentil productivity worldwide. Understanding the genetic basis of salt tolerance is vital to develop tolerant varieties. A diversity panel consisting of 276 lentil accessions was screened in a previous study through traditional and image-based approaches to quantify growth under salt stress. Genotyping was performed using two contrasting methods, targeted (tGBS) and transcriptome (GBS-t) genotyping-by-sequencing, to evaluate the most appropriate methodology. tG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Genome‐wide association studies (GWAS) have been extensively used in plant science to identify genetic markers and candidate genes associated with a range of traits (Tibbs Cortes et al, 2021). In lentil, GWAS has been used to identify markers associated with days to flower, seeds per pod, 100 seed weight, salinity tolerance, Aphanomyces root rot resistance, iron (Fe) and zinc (Zn) concentrations, prebiotic carbohydrate concentrations, and AA concentrations quantified by near‐infrared spectroscopy (Dissanayake et al, 2021; Hang, 2021; Hang et al, 2022; Johnson et al, 2021; Kumar et al, 2019; Ma et al, 2020; Rajendran et al, 2021). Protein‐quality traits have also been explored via GWAS in cereal crops (Chen et al, 2016) and legumes such as chickpea (Karaca et al, 2019) and common bean (Katuuramu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Genome‐wide association studies (GWAS) have been extensively used in plant science to identify genetic markers and candidate genes associated with a range of traits (Tibbs Cortes et al, 2021). In lentil, GWAS has been used to identify markers associated with days to flower, seeds per pod, 100 seed weight, salinity tolerance, Aphanomyces root rot resistance, iron (Fe) and zinc (Zn) concentrations, prebiotic carbohydrate concentrations, and AA concentrations quantified by near‐infrared spectroscopy (Dissanayake et al, 2021; Hang, 2021; Hang et al, 2022; Johnson et al, 2021; Kumar et al, 2019; Ma et al, 2020; Rajendran et al, 2021). Protein‐quality traits have also been explored via GWAS in cereal crops (Chen et al, 2016) and legumes such as chickpea (Karaca et al, 2019) and common bean (Katuuramu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Wild relatives of lentil possess valuable genes conferring resistance and tolerance to biotic and abiotic stresses ( Gupta et al, 2011 ) and recent studies have reported promising results in the use of lentil wild relatives for breeding purposes (i.e., lentil rust, powdery mildew, or fusarium wilt resistance and drought and cold tolerance) ( Mohar et al, 2020 ; Asghar et al, 2021 ). Other works point to the identification of novel genes or alleles involved in overcoming salinity tolerance and incorporating them into commercial lentils, as the path to increase productivity ( Dissanayake et al, 2021 ), so the exploitation of genetic resources of lentil wild relatives gains special interest. The crossability among the different species of lentils has been widely studied, placing Lens culinaris ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Genomewide association study (GWAS) was first demonstrated in lentil to reveal marker-trait association for Aphanomyces root rot resistance (Ma et al, 2020). Later, GWAS was used for identification of marker for improtant agronomic traits (Rajendran et al, 2021), prebiotic carbohydrates (Johnson et al, 2021) and salt tolerance (Dissanayake et al, 2021).…”
Section: Resistance Breeding In Lentilmentioning
confidence: 99%
“…Ma et al (2020) used GBS strategy to genotype a RIL population and identified 19 QTLs for Aphanomyces root rot resistance in lentil. In parallel, genome wide association studies (GWAS) were also practiced in lentil for identification of marker-trait association for Aphanomyces root rot resistance (Ma et al, 2020), agronomic traits (Rajendran et al, 2021), prebiotic carbohydrates (Johnson et al, 2021) and salt tolerance (Dissanayake et al, 2021). All these above examples of detecting QTLs/associated SNPs for a targeted trait in lentil have shown promise to apply genomic selection to select genotypes with multiple disease resistance.…”
Section: Genomics Assisted Breeding In Lentilmentioning
confidence: 99%